Governança pública e institucionalização nas fundações de apoio às instituições federais de ensino superior: um estudo de caso - Oliveira, Mayara Nascimento de (2023)
Beneath the theoretical aspects of Institutionalism, Legitimacy, Neo-institutionalism, Isomorphism, Public Governance, and Support Foundations, this study analyzes the influence of the Federal University of Sergipe (UFS) on current public governance practices at Research and Extension Support Foundation of Sergipe (FAPESE), through institutionalization. The research was structured using a qualitative, exploratory-descriptive approach. Therefore, through the research strategy of the case study, a survey of public governance was conducted about FAPESE based on the questionnaire used by the The Federal Court of Accounts - Brazil (TCU) to define the Profile of Public Governance and Management - Cycle 2021 of its jurisdictional entities and compare with the profile shown by UFS under the same indicators. It considered the issues related to Leadership, Strategy, and Control linked to iGovPub (organizational public governance index). Based on that, according to the model of Tolbert and Zucker (1998), the stage of institutionalization of existing public governance practices at FAPESE under the influence of UFS was analyzed. Therefore, there were interviews with managers from both institutions that are part of the Permanent Commission for Project Oversight involving the Federal University of Sergipe and the Support Foundations (CPAP), in addition to documentary research and participant observation. Thus, the study concluded that the volume of public governance practices carried out at FAPESE is small, and these receive little influence from the UFS, with the first stage, habituation, being the one that best characterizes this institutionalization process. In addition, the Foundation 's practices must seek improvement, maintaining the level of quality while reducing its volatility as market pressure or new legislation arises. This analysis resulted in intervention recommendations aimed at more efficient development of FAPESE's public governance.